Rural Nuring in Canada: A Voice Unheard - Deirdre Jackman; Florence Myrick; Olive J. Yonge (Rural Nurse Organization; Binghamton University, 2012)
Historically, in Canada, rural nurses provided health care that incorporated not only care of disease processes and acute illness but also care related to social and political aspects of need and advocacy. With the advent of urbanized, acute hospital care and the focus of disease and cure, the role of the rural nurse was diminished. The purpose of this paper is to explore the role of the rural nurse within the context of the Canadian rural populations for whom they care and more specifically to examine how the effects of marginalization and health policy and decision making processes contributed and may continue to contribute negatively to marginalization. The implications of not recognizing or marginalizing rural nurses may once again remove or negate their voice, affect their health care influence and impact the central role of the rural nurse in providing holistic care for and with the rural populations they serve.